40.2k views
5 votes
Simplify 6-(9x+7)+2x=


2 Answers

2 votes

Answer:

-7x - 1

Explanation:

Well to start off we have to multiply because of the - symbol at the start of the parenthesis.

So - * 9x is -9x and - * 7 is -7 so our equation looks like this now
6-9x-7+2x=.

Now we have to combine like terms so 6 + -7 is -1 and -9x + 2x is -7x.

So now our equation looks like this
-7x-1=.

So that is simplifued all the way.

User Rahil
by
5.6k points
0 votes

Answer:

-7x-1

Explanation:

6-(9x+7)+2x

-(9x+7): -9x-7

= 6-9x-7+2x

6-9x-7+2x=-7x-1

-7x-1

User Sisko
by
4.7k points